The Potential Role of Dysfunctions in Neuron-Microglia Communication in the Pathogenesis of Brain Disorders - Chamera, Katarzyna; Trojan, Ewa; Szuster-Głuszczak, Magdalena; Basta-Kaim, Agnieszka (Current Neuropharmacology, 2020)
The bidirectional communication between neurons and microglia is fundamental for the proper functioning of the central nervous system (CNS). Chemokines and clusters of differentiation (CD) along with their receptors represent ligand-receptor signalling that is uniquely important for neuron – microglia communication. Among these molecules, CX3CL1 (fractalkine) and CD200 (OX-2 membrane glycoprotein) come to the fore because of their cell-type-specific localization. They are principally expressed by neurons when their receptors, CX3CR1 and CD200R, respectively, are predominantly present on the microglia, resulting in the specific axis which maintains the CNS homeostasis. Disruptions to this balance are suggested as contributors or even the basis for many neurological diseases. In this review, we discuss the roles of CX3CL1, CD200 and their receptors in both physiological and pathological processes within the CNS. We want to underline the critical involvement of these molecules in controlling neuron – microglia communication, noting that dysfunctions in their interactions constitute a key factor in severe neurological diseases, such as schizophrenia, depression and neurodegeneration-based conditions.
Keywords: Alzheimer' s disease